A computational experiment on elicitation task bias in time preference. (2015) - Tokarchuk, Oksana; Gabriele, Roberto
Experimental results from research on time preference are often controversial. We propose a systematic investigation of choice task in multiple price list (MPL) format, frequently used for experiments on time preference, based on a computer simulation analysis. Our experiments with artificial subjects demonstrate that elicited discount rates are highly dependent on the structure of elicitation task. Indeed, implementing the choice task in MPL with nominal structure provides observations of hyperbolic discounting. Choice task in MPL with interest rates structure leads to elicitations of discount rates compatible with exponential discounting. The comparison between discount rates elicited with artificial and human subjects suggests that the behaviour of human subjects in experiments with MPL can be described by the simple rules of positive discounting and anchoring. Experimental procedures related with MPL setting has to take into account the results and modify the task accordingly.